2021
DOI: 10.1108/jeet-02-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between academic integrity of online university students and its effects on academic performance and learning quality

Abstract: Purpose This paper aims to investigate the relationship between academic integrity of online university students and its effects on academic performance and learning quality. The first hypothesis aimed to see if there is statistically significant relationship between academic honesty of students taking online classes and their apparent academic performance. The second hypothesis aimed to see if there is a statistically significant difference in academic integrity among male and female students. The third hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…are multiple-choice or true/false. Moreover, the results agree with studies that confirmed that students prefer e-exams because they provide marks and feedback more quickly, and help them to improve their learning and understanding of the content of the curriculum compared to traditional paper exams [6,7,27,44]. In contrast, however, some of the students' responses to the questionnaire items showed negative attitudes towards the implementation and application of e-exams at their university during the Covid-19 pandemic spread.…”
Section: Plos Onesupporting
confidence: 83%
“…are multiple-choice or true/false. Moreover, the results agree with studies that confirmed that students prefer e-exams because they provide marks and feedback more quickly, and help them to improve their learning and understanding of the content of the curriculum compared to traditional paper exams [6,7,27,44]. In contrast, however, some of the students' responses to the questionnaire items showed negative attitudes towards the implementation and application of e-exams at their university during the Covid-19 pandemic spread.…”
Section: Plos Onesupporting
confidence: 83%
“…Additional sampling therefore could only benefit the study, improve the instrument and enable adjustments and modifications wherever required. During the present COVID-19 era, it would be interesting to perform further research and collect more responses to identify whether findings follow the pattern that has been collected up to date, especially when and where distance learning (Ayoub/Al-Salim and Aladwan, 2021) is blended and implemented in PE. It should also be noted that the findings of this study were derived from public schools and are reliable for them only.…”
Section: Discussionmentioning
confidence: 99%
“…At the pandemic’s onset, Iraqi online students perceived that online education would be easier than FTF (Kurdistan et al , 2020). Contrastingly, Middle Eastern undergraduate students indicated that online lectures are not as exciting as FTF lectures and are difficult to learn from (Maida and Aladwan, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%